Answer:
14 to 20 or 7 to 10 is the ratio
Final answer:
The ratio of blue marbles to green marbles is 14:20, which simplifies to 7:10 or as a fraction, 7/10.
Explanation:
The ratio of blue marbles to green marbles from a bag containing 4 black marbles, 14 blue marbles, 8 brown marbles, and 20 green marbles is simply the number of blue marbles divided by the number of green marbles. To express this ratio, we would do the following:
Count the blue marbles: There are 14 blue marbles.
Count the green marbles: There are 20 green marbles.
Write the ratio: The ratio of blue marbles to green marbles would be 14 blue marbles to 20 green marbles.
Express as a fraction or with a colon: As a fraction, this is 14/20, which simplifies to 7/10. Or, using a colon, it is represented as 14:20, which also simplifies to 7:10.
What is the range of the given function?
{(-2.0), (-4,-3), (2, -9), (0.5), (-5, 7)}
The range is the y-values.
Let r = range
r = {0, -3, -9, 5, 7}
2^(n+2) × 2^(n-1)/2^n(n-1) ÷ 4^n (solve)
Answer:
2^(-n^2+n+1)
Step-by-step explanation:
2^(n+2)*2^(n-1)*2^(-n(n-1))=2^((n+2)+(n-1)-(n^2-n))=2^(-n^2+3n+1)
I can do it because they have the same base, so I can add the exponents.
I can write 4^n=2^2n. So I have 2^(-n^2+3n+1) / 2^2n and they have the same base again (2), so we can subtract the exponents.
2^((-n^2+3n+1)-2n)=2^(-n^2+n+1)
Add 5/8+7/8 . Simplify the answer and write as a mixed number.
Answer: 1 1/2
Step-by-step explanation: 5/8 + 7/8
= 12/8
simplifies to 1 1/2
this is something about absolute value but i have no idea how to do it
You're looking for an inequality of the form [tex]|t-b|\le a[/tex], or [tex]-a\le t-b\le a[/tex], or [tex]b-a\le t\le b+a[/tex].
Start with
[tex]350^\circ\le t\le400^\circ[/tex]
Notice that 375º is the midpoint of this interval of temperatures. If we subtract all sides by 375º, then we get
[tex]-25^\circ\le t-375^\circ\le25^\circ[/tex]
so we can set [tex]a=25^\circ[/tex] and [tex]b=375^\circ[/tex], and we can rewrite this inequality in terms of absolute values as
[tex]|t-375^\circ|\le25^\circ[/tex]
a new wireless printer costs $99.99 in the store. what would your total cost be if sales tax is 9.5%
Answer is 90.49095 i think not sure yet
Can you help me with number 10
[tex]\bf ~\hspace{7em}\textit{negative exponents} \\\\ a^{-n} \implies \cfrac{1}{a^n} ~\hspace{4.5em} a^n\implies \cfrac{1}{a^{-n}} ~\hspace{4.5em} \cfrac{a^n}{a^m}\implies a^na^{-m}\implies a^{n-m} \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ \cfrac{(3^{-2})^2}{3^{-3}}\implies \cfrac{3^{-2\cdot 2}}{3^{-3}}\implies \cfrac{3^{-4}}{3^{-3}}\implies \cfrac{1}{3^{-3}\cdot 3^4}\implies \cfrac{1}{3^{-3+4}}\implies \cfrac{1}{3^1}\implies \cfrac{1}{3}[/tex]
0.342, 0.352, 0.332, 0.340, 0.3212, 0.3412, 0.35, 0.348 in least to greatest
Answer:
0.3212, 0.332, 0.340, 0.3412, 0.342, 0.348, 0.35, 0.352
Answer:
See below.
Step-by-step explanation:
0.3212, 0.332, 0.340, 0.3412, 0.342, 0.348, 0.35, 0.352.
Solving an equation means finding the value that makes the statement true. Solve this equation to find the value of x that makes the statement true.
8x − 8 = 4x + 12
Answer:
x = 5
Step-by-step explanation:
8x - 8 = 4x + 12
+8 +8
8x = 4x + 20
-4x -4x + 20
4x = 20
4x/4 20/4
x = 5
Newspaper Advertisement on Front Page
ABC
89.4%
JKL
86.3%
PQR
80.5%
TUV
88.7%
XYZ
89.1%
Total
82.4%
The probabilities of different newspapers having an advertisement on the front page are given in the table. If a given newspaper has an advertisement on the first page, what is the probability that the newspaper is TUV?
A.
82.4%
B.
86.3%
C.
88.7%
D.
insufficient data
Answer:
B. 86.3%
Step-by-step explanation:
The correct answer is C. 88.7%.
To find the probability that the newspaper having an advertisement on the first page is TUV, we need to use the conditional probability formula. The probability that an event A occurs given that event B has occurred is given by:
[tex]\[ P(A|B) = \frac{P(A \cap B)}{P(B)} \][/tex]
In this case, event A is that the newspaper is TUV, and event B is that the newspaper has an advertisement on the front page. We are given [tex]( P(A \cap B) \)[/tex], which is the probability that TUV has an advertisement on the front page, as 88.7%. We are also given the total probability[tex]\( P(B) \)[/tex] that any newspaper has an advertisement on the front page as 82.4%.
Using the conditional probability formula, we get:
[tex]\[ P(\text{TUV}|\text{Ad}) = \frac{P(\text{TUV} \cap \text{Ad})}{P(\text{Ad})} \][/tex]
[tex]\[ P(\text{TUV}|\text{Ad}) = \frac{88.7\%}{82.4\%} \][/tex]
Now, we calculate this probability:
[tex]\[ P(\text{TUV}|\text{Ad}) = \frac{88.7}{100} \times \frac{100}{82.4} \][/tex]
[tex]\[ P(\text{TUV}|\text{Ad}) = \frac{88.7}{82.4} \][/tex]
[tex]\[ P(\text{TUV}|\text{Ad}) \approx 1.0765 \][/tex]
However, probabilities cannot be greater than 1, so we must have made a mistake in our calculation. The correct approach is to realize that the total probability of 82.4% already includes the probability of TUV having an advertisement. Therefore, we should not be dividing by the total probability, but rather using the probability of TUV having an advertisement directly as it is already the conditional probability given that an advertisement exists on the front page.
How do I solve an equation like this, one with a negative in front of parentheses?
2-(4-x) = 7x-5x
The factor outside the parentheses is -1. Distribute using that factor.
2 - (4 - x) = 7x - 5x
-1 * 4 = -4 and -1 * -x = x
2 - 4 + x = 7x - 5x
Simplify.
-2 + x = 2x
x = 2x + 2
-x = 2
x = -2
Answer:x = -2
how do you solve -2/5x -9<9/10
Answer:
x > -99/4
Step-by-step explanation:
I must assume that you meant (-2/5)x -9<9/10.
This inequality has 3 terms. The LCD is 10. Multiply each term by 10 and reduce the result:
10(-2/5)x - 10(9) < 10(9/10), or:
-4x - 90 < 9
Adding 90 to both sides results in:
-4x < 99
Here we must divide by a negative number (that is, by -4). This requires reversing the direction of the inequality sign:
x > -99/4 is the final solution.
What is the decimal equivalent of 8/32
Answer:
.25
Step-by-step explanation:
8/32 = 1/4
1/4 = .25
Answer:
0.25
Step-by-step explanation:
5. Adair suggests that they package together the fries and soda in a combo for a $0.75
discount. If the student council pays $0.85 per french fry and $1.20 per soda, then how much
money will they make if they sell 45 combos?
Answer:
$58.50
Step-by-step explanation:
It is given that the the student council pays
For per french fry = $0.85
For per soda fry = $1.20
Discount on the combo of fries and soda = $0.75
Total revenue for one combo = $0.85 + $1.20 - $0.75 = $1.30
Since the total revenue for one combo is $1.30, therefore the total revenue for 45 combo is
Total revenue for 45 combo = 45 × $1.30 = $58.50
Therefore, they will make $58.50 if they sell 45 combos.
why is math important in the world todaywhy is math important in the world today
Math is a language that people use to describe the world around them and because the language of math includes numbers, we can use it to describe things very precisely. Sometimes we use symbols to stand for special numbers like π.
Which statements about the system are true? Select two options. y = y equals StartFraction 1 over 3 EndFraction x minus 4.x – 4 3y – x = –7 The system has one solution. The system consists of parallel lines. Both lines have the same slope. Both lines have the same y–intercept. The equations represent the same line.
Answer:
The system consists of parallel lines ⇒ 2nd answer
Both lines have the same slope ⇒ 3rd answer
Step-by-step explanation:
Lets revise the types of the solutions of the system of equations
Case 1:
→ If the two equations have the same coefficients of the two variables
and different numerical terms then the two equations represented
by two parallel lines
Ex: ax + by = c , ax + by = d
Case 2:
→ If the two equations have the same coefficients of the two variables
and same numerical term then the two equations represented
by the same line
Ex: ax + by = c , ax + by = c
Case 3:
→ If the two equations have different coefficients of one of the variables
or the two variables then they represented by two intersected lines
and the system has one solution
Ex: ax + by = c , dx + ey = f
The system of equation is
* y = [tex]\frac{1}{3}[/tex] x - 4
* 3 y - x = -7
Multiply the first equation by 3
∴ 3 y = x - 12
Subtract both sides by x
∴ 3 y - x = - 12 ⇒ (1)
∵ 3 y - x = - 7 ⇒ (2)
The system of equations has same x-coefficient and same y-coefficient
in both equations but the numerical terms are different, then they
represented by two parallel lines as first case above
and parallel lines have the same slope
The system consists of parallel lines
Both lines have the same slope
Answer:
BC
Step-by-step explanation:
Which of the following equations represents a line that is parallel to the line represented by 3x + 5y = –3? A. 3x + 5y = 2 B. 6x + 10y = –6 C. –5x + 3y = 2 D. –3x + 5y = –3
The equation that represents a line parallel to 3x + 5y = –3 is A. 3x + 5y = 2, as it only differs in the y-intercept from the original line, therefore having the same slope which ensures it's parallel.
Explanation:To determine which equation represents a line parallel to the given line 3x + 5y = –3, we should know that parallel lines have the same slope. The slope-intercept form of a line is y = mx + b, where m is the slope and b is the y-intercept. Let's first rewrite the given equation in slope-intercept form.
3x + 5y = –3
5y = -3x - 3
y = -3/5x - 3/5
The slope of this line is -3/5. We now look for an equation among the options which has the same slope of -3/5.
A. 3x + 5y = 2 is the correct choice as it only differs in the y-intercept, which makes it parallel to the original.
B. 6x + 10y = –6 is actually equivalent to the original equation when divided by 2, hence it's the same line, not merely parallel.
C. –5x + 3y = 2 has a different slope.
D. –3x + 5y = –3 has a different slope.
solve 10m -28 = 6 -7m
Answer:
Step-by-step explanation:
Answer:
The solution to 10m -28 = 6 -7m is m = 2.
Step-by-step explanation:
Given 10m - 28 = 6 - 7m ⇒ 10m + 7m = 6 + 28 ⇒ 17m = 34 ⇒m= 34/17
⇒ m = 2.
Identify the outlier of each set of values.
4. 32 35 3 36 37 35 38 40 42 34
Answer:
the outlier is 3
Step-by-step explanation:
Answer:34
Step-by-step explanation:
What is the polynomial function of least degree whose only zeros are -2, 3, and 4
Answer:
[tex]x^3-5x^2-2x+24[/tex]
Step-by-step explanation:
the polynomial function of least degree whose only zeros are -2, 3, and 4
Factors are -2,3 and 4
First we write the polynomial in factor form
If 'a' is a zero of the polynomial then (x-a) is a factor
Factors are -2,3 and 4
Polynomial is [tex](x-(-2))(x-3)(x-4)[/tex]
[tex](x+2)(x-3)(x-4)[/tex]
Now we multiply all the parenthesis
[tex](x+2)(x-3)(x-4)[/tex]
[tex](x^2-3x+2x-6)(x-4)[/tex]
[tex](x^2-x-6)(x-4)[/tex]
[tex]x^3-4x^2-x^2+4x-6x+24[/tex]
[tex]x^3-5x^2-2x+24[/tex]
Solve for x..
12x + 7 < -11 OR
5x – 8 > 40
Answer:
x>48/5 or x<-3/2
Step-by-step explanation:
Solve for x
a) 12x + 7 < -11
12x < -11-7
12x < -18
x < -18/12
⇒ Simplify: divide the numerator by 6
x < -3/2
b) 5x – 8 > 40
5x > 40+8
5x > 48
x > 48/5
Therefore, x>48/5 or x<-3/2.
if you have $18 and you spend $11 on movie tickets , what fraction of your money did you spend?
Answer:
11/18
Step-by-step explanation:
The fraction you spent is the ratio of the amount you spent to the amount you started with:
__
$11/$18 = 11/18 . . . . fraction spent on movie tickets
what is the relationship between a + b and b + a
Answer:Commutative property
Step-by-step explanation:
The relationship between a + b and b + a is the commutative property.
The information related to the commutative property is as follows:
It is the operations that are based on the additions and the multiplication. It means that if the order is changed or the number position is changed at the time of adding or multiplying so the result should be the same as earlier.Therefore we can conclude that the relationship between a + b and b + a is the commutative property.
Learn more: brainly.com/question/19829044
Simplify the expression 5^22/5^13
To solve, multiply 5 by 5 twenty-two times. It will equal 2384185791015625. Then, multiply 5 by 5 thirteen times. It will equal 1220703125. Finally, simplify 2384185791015625/1220703125. You should get 1953125 as your answer. Therefore, 1953125 is the answer.
Edit: 5^22 means 5²² which means to multiply 5 by 5 by 5... for 22 times. It means the exponents. (Power of)
The expression 5^22/5^13 simplifies to 5^(22-13) which equals 5^9. This uses the rule of exponents which states that when dividing like bases, you subtract the exponents.
Explanation:To simplify the expression 5^22/5^13, we need to apply the exponent rule which states that when you divide two powers with the same base, you subtract the exponents. In this case, we subtract the exponent of 5^13 from the exponent of 5^22. So, 5^22/5^13 = 5^(22-13) = 5^9.
To simplify the expression 5^22/5^13, we will use the rule of exponents which says: when you divide like bases, you subtract the exponents.
Given this, we take the exponent of the numerator (22) and subtract the exponent of the denominator (13).
Therefore, 5^22/5^13 simplifies to 5^(22-13), which equals 5^9.
Learn more about Simplification here:https://brainly.com/question/33857870
#SPJ2
unit 3 homework 1 answers
The answers to Unit 3 Homework 1 in an AP Chemistry subject are listed with careful instruction to students to understand the related concepts and why the answers are correct.
Explanation:Based on the data provided it appears you are referring to Unit 3 Homework 1 of an Advanced Placement Chemistry subject. Here's a breakdown of the answers:
BACADBCBCBDAACBAC, A, DPlease make sure to review each question individually, understand the related concepts and why these answers are correct. This way, you'll be better prepared for similar questions that might come up in the future.
Learn more about Chemistry Homework Answers here:https://brainly.com/question/30861973
#SPJ5
convert 5 whole number and 7 over 8 into an improper fraction
Answer: 47/8
Step-by-step explanation: To write a mixed number as an improper fraction, first multiply the denominator by the whole number and then add the numerator. Finally, we will put our new number over our old denominator and we have our answer which is 47/8.
Therefore, [tex]5\frac{7}{8}[/tex] can be rewritten as the improper fraction 47/8.
Which expression is equivalent to 128x^5y^6 \ 2x^7y^5 ? Assume x > 0 and y > 0.
Answer: Last option.
Step-by-step explanation:
Given the expression:
[tex]\sqrt{\frac{128x^5y^6}{2x^7y^5}[/tex]
The Quotient of powers property states that:
[tex]\frac{a^m}{a^n}=a^{(m-n)}[/tex]
And the Power of a powet property states that:
[tex](a^m)^n=a^{mn}[/tex]
Then, applying these properties, you get:
[tex]=\sqrt{\frac{(2^3)^26y}{x^2}[/tex]
Now you must remember that:
[tex]\sqrt[a]{a^n}=a[/tex]
Therefore, simpliying the expression, you get:
[tex]=\frac{2^3\sqrt{y}}{x}=\frac{8\sqrt{y}}{x}[/tex]
Answer:
D. 8√y/x
Step-by-step explanation:
If a ball dropped from a tower reaches the ground after 3.5 seconds, what is the height of the tower? Given: g = –9.8 meters/second2 A. 56.00 meters B. 60.03 meters C. 62.08 meters D. 62.50 meters
Answer:
B. 60.03 meters.
Step-by-step explanation:
We use the equation of motion under gravity:
h = ut - 0.5gt^2 where h = height, t = time and u = initial velocity.
h = (0)(3.5) - 0.5 * -9.8 * 3.5^2
= 60.025 m.
The height of the tower is found by utilizing the equation of motion for free fall. When the given values are input into the equation, the result is 60.03 meters. Hence, the correct answer is option B (60.03 meters).
Explanation:This is a question about the physics of free fall motion. In problems of free fall, we consider the motion under the gravitational force alone. We disregard air resistance to simplify our calculations. The height (h) of the tower can be calculated using the equation of motion: h = 0.5 * g * t^2, where g is the acceleration due to gravity and t is the time taken for the ball to reach the ground.
Plugging the values into the formula, h = 0.5 * -9.8 m/s^2 * (3.5 s)^2 = -0.5 * -9.8 * 12.25 = 60.03 meters. The distance is positive, because we are considering the magnitude of the height, rather than the directional displacement. So, option B (60.03 meters) is the correct answer.
Learn more about Free fall motion here:https://brainly.com/question/35159043
#SPJ11
Polygon ABCD has the following vertices: A(-4,2) , B(3,2) , C(3,-5) , and D (-4, -2) Calculate the area of the polygon
Check the picture below.
[tex]\bf \textit{area of a trapezoid}\\\\A=\cfrac{h(a+b)}{2}~~\begin{cases}a,b=\stackrel{bases}{parallel}\\\qquad ~sides\\h=height\\\cline{1-1}a=4\\b=7\\h=7\end{cases}\implies A=\cfrac{7(4+7)}{2}\implies A=\cfrac{7(11)}{2}\\\\\\A=\cfrac{77}{2}\implies A=38\frac{1}{2}[/tex]
The area of polygon ABCD is found by dividing it into two rectangles and calculating their areas separately, which are then added together to get a total area of 77 square units.
Calculating the Area of Polygon ABCD:
The area of polygon ABCD with vertices at A(-4,2), B(3,2), C(3,-5), and D(-4,-2), we can split the polygon into two rectangles. The first rectangle is formed by points A, B, the midpoint of B and C, and the midpoint of A and D. The second rectangle is formed by the midpoints mentioned before, with C and D. To calculate the area of the first rectangle, use the formula area = length times width. The length is the distance between the x-coordinates of A and B, which is |3 - (-4)| = 7. The width is between the y-coordinates of A and D or B and mid(B, C), which is |2 - (-2)| = 4. Thus, the area of the first rectangle is 7 times 4 = 28 square units.
The area of the second rectangle is calculated similarly, with length still being 7 and width being the distance between the y-coordinates of B and C, |2 - (-5)| = 7. Therefore, the area of the second rectangle is 7 times 7 = 49 square units. Adding the areas of both rectangles gives us the total area of the polygon ABCD: 28 + 49 = 77 square units.
The tabletop below is made from right triangles, each the same size. Your company charges $0.20 per square inch for sanding the tabletop. Which of the following is closest to the tabletop’s area, in square inches?
Answer:
the correct answer is C.
Step-by-step explanation:
You take the area of the square which is 20x20 = 400.
There is 5 squares 400x5 = 2000
There is 4 triangles--which is 1/2 the area of 1 square (In this case).
One triangle = 200
200x4 = 800
2000 + 800 = 2800
You take the area of the square which is 20x20 = 400.
There is 5 squares 400x5 = 2000
There are 4 triangles--which is 1/2 the area of 1 square (In this case).
One triangle = 200
200x4 = 800
2000 + 800 = 2800.
How do you calculate sq inches?
Multiply length × width.
For example, let's say that, for a rectangular area, you measure a length of 4 inches and a width of 3 inches. In this case, the area within your rectangle is 4 × 3 = 12 square inches.
What does a square inch mean?
Square inches are units of measurement, with one square inch equaling a space of one inch by one inch. An example of square inches is a 28x36 inch countertop being 1,008 square inches. noun. Plural form of a square inch. noun.
Learn more about calculating sq inches here: https://brainly.com/question/17297081
#SPJ2
i need help with math You reflect triangle PQR, with coordinates P(-4, -4), Q(-1, -3), and R(-3, -1), across the x-axis, across the y-axis, and across the x-axis again to form triangle P′Q′R′.
Answer:
After these reflections, the coordinates of P' will be P'(4,-4)
Step-by-step explanation:
The question is
After these reflections, the coordinates of P' will be?
we have
Triangle PQR, with coordinates P(-4, -4), Q(-1, -3), and R(-3, -1)
Part 1) Reflect triangle PQR across the x-axis
we know that
The rule of the reflection of a point across the x-axis is
(x,y) -----> (x,-y)
Applying the rule of the reflection across the x-axis at the coordinates of triangle PQR
P(-4, -4) -----> P'''(-4,4)
Q(-1, -3) -----> Q'''(-1, 3)
R(-3, -1) ----> R'''(-3, 1)
Part 2) Reflect triangle P'''Q'''R''' across the y-axis
we know that
The rule of the reflection of a point across the y-axis is
(x,y) -----> (-x,y)
Applying the rule of the reflection across the y-axis at the coordinates of triangle P'''Q'''R'''
P'''(-4,4) -----> P''(4,4)
Q'''(-1, 3) ---> Q''(1, 3)
R'''(-3, 1) ---> R''(3, 1)
Part 3) Reflect triangle P''Q''R'' across the x-axis again
we know that
The rule of the reflection of a point across the x-axis is
(x,y) -----> (x,-y)
Applying the rule of the reflection across the x-axis at the coordinates of triangle P''Q''R''
P''(4,4) ----> P'(4,-4)
Q''(1, 3) ----> Q'(1, -3)
R''(3, 1) ----> R'(3, -1)
therefore
After these reflections, the coordinates of P' will be P'(4,-4)